The Curious Case of the British Avant-Garde - Drag, Wojciech (Hungarian Journal of English and American Studies, 2020)
Book review:Mitchell, Kaye, and Nonia Williams, eds. British Avant-Garde Fiction of the 1960s. Edinburgh: Edinburgh UP, 2019. 272 pages. ISBN 978147443619 9. Hb. £80.00.